Parrots as key multilinkers in ecosystem structure and functioning - Blanco, Guillermo (Ecol Evol, 2015)
Mutually enhancing organisms can become reciprocal determinants of their distribution, abundance, and demography and thus influence ecosystem structure and dynamics. In addition to the prevailing view of parrots (Psittaciformes) as plant antagonists, we assessed whether they can act as plant mutualists in the dry tropical forest of the Bolivian inter‐Andean valleys, an ecosystem particularly poor in vertebrate frugivores other than parrots (nine species). We hypothesised that if interactions between parrots and their food plants evolved as primarily or facultatively mutualistic, selection should have acted to maximize the strength of their interactions by increasing the amount and variety of resources and services involved in particular pairwise and community–wide interaction contexts. Food plants showed different growth habits across a wide phylogenetic spectrum, implying that parrots behave as super‐generalists exploiting resources differing in phenology, type, biomass, and rewards from a high diversity of plants (113 species from 38 families). Through their feeding activities, parrots provided multiple services acting as genetic linkers, seed facilitators for secondary dispersers, and plant protectors, and therefore can be considered key mutualists with a pervasive impact on plant assemblages. The number of complementary and redundant mutualistic functions provided by parrots to each plant species was positively related to the number of different kinds of food extracted from them. These mutually enhancing interactions were reflected in species‐level properties (e.g., biomass or dominance) of both partners, as a likely consequence of the temporal convergence of eco‐(co)evolutionary dynamics shaping the ongoing structure and organization of the ecosystem. A full assessment of the, thus far largely overlooked, parrot–plant mutualisms and other ecological linkages could change the current perception of the role of parrots in the structure, organization, and functioning of ecosystems.